Exploring Morphological and Cultural Adaptation in the Translation of the Legend of Pulau Senua - Selli Natasha; Dimas Adika; Widyasari Widyasari (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2025)
This study explores the morphological and cultural adaptation strategies used in the English translation of the Indonesian folktale “The Legend of Pulau Senua.” The research aims to identify how affixation, derivation, and culture-specific elements (realia) are transferred across languages. Using a qualitative-descriptive method and translation theories from Nida, Newmark, Venuti, Baker, and Osimo, this paper analyzes selected text segments from both the source and target versions. Findings show that Indonesian morphological features are often simplified or replaced due to structural differences with English. Cultural elements are adapted using strategies such as substitution, explicitation, and idiomatic paraphrasing. Additionally, this study emphasizes how important it is to maintain symbolism and character development to maintain moral and narrative depth. The analysis confirms that effective translation of folktales requires more than linguistic accuracy it also demands cultural sensitivity and narrative awareness. This research contributes practical insights for translators working with culturally rich texts.